PENINGKATAN KEPUASAN PESERTA TERHADAP LAYANAN INFORMASI BPJS KESEHATAN MELALUI MEDIA: APAKAH EFEKTIF? - Nahdiana Nahdiana; Alimuddin Unde; Sudirman Nasir; Yunus Amar (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
Abstract Public Understanding of the National Health Insurance Program (JKN) is still lacking due to the limitations of health information services from the government. This study aims to find out whether the use of media in disseminating JKN Program information effectively provides information service satisfaction to BPJS Kesehatan participants. The study used a quantitative design with survey explanation methods. The population in this study was a non-PBI Health BPJS participant (not a Contribution Assistance Recipient) with a PPU category (Wage Earner Worker) of 405 people. Data retrieval techniques through questionnaires given to respondents through a google form. The data is processed using smart PLS and analyzed with the SEM (Structural Equation Model) approach. The results showed that the media had a positive and significant effect on participants' satisfaction which can be seen from the value of t-statistical media to satisfaction of 3.13 > 1.96 or p-value value of 0.00 < 0.05 and track coefficient value of 0.148 which indicates that the media aspect affects the media satisfaction of participants. Based on the results of the study, it can be concluded that the use of effective media provides satisfaction to BPJS Kesehatan participants. The results of this study are expected to be used as a consideration for BPJS Kesehatan to use more fragmented media to disseminate information taking into account the condition/ability of the community. Keywords: BPJS Health, information services, JKN Program, media, participant satisfaction